Attenuation of Plasmodium falciparum in vitro drug resistance phenotype following culture adaptation compared to fresh clinical isolates in Cambodia. (December 2015) - Chaorattanakawee, Suwanna; Lanteri, Charlotte; Sundrakes, Siratchana; Yingyuen, Kritsanai; Gosi, Panita; Chanarat, Nitima; Wongarunkochakorn, Saowaluk; Buathong, Nillawan; Chann, Soklyda; Kuntawunginn, Worachet; Arsanok, Montri; Lin, Jessica; et al.
Abstract Background There is currently no standardized approach for assessing in vitro anti-malarial drug susceptibility. Potential alterations in drug susceptibility results between fresh immediate ex vivo (IEV) and cryopreserved culture-adapted (CCA)Plasmodium falciparum isolates, as well as changes in parasite genotype during culture adaptation were investigated. Methods The 50 % inhibitory concentration (IC50 ) of 12P. falciparum isolates from Cambodia against a panel of commonly used drugs were compared using both IEV and CCA. Results were compared using both histidine-rich protein-2 ELISA (HRP-2) and SYBR-Green I fluorescence methods. Molecular genotyping and amplicon deep sequencing were also used to compare multiplicity of infection and genetic polymophisms in fresh versus culture-adapted isolates. Results IC50 for culture-adapted specimens were significantly lower compared to the original fresh isolates for both HRP-2 and SYBR-Green I assays, with greater than a 50 % decline for the majority of drug-assay combinations. There were correlations between IC50 s from IEV and CCA for most drugs assays. Infections were nearly all monoclonal, with little or no change in merozoite surface protein 1 (MSP1), MSP2, glutamate-rich protein (GLURP) or apical membrane antigen 1 (AMA1) polymorphisms, nor differences inP. falciparum multidrug resistance 1 gene (PfMDR1) copy number or single nucleotide polymorphisms following culture adaptation. Conclusions The overall IC50 reduction combined with the correlation between fresh isolates and culture-adapted drug susceptibility assays suggests the utility of both approaches, as long as there is consistency of method, and remaining mindful of possible attenuation of resistance phenotype occurring in culture. Further study should be done in higher transmission settings where polyclonal infections are prevalent.